Aspek Psikiatrik pada Kekerasan Terhadap Tenaga Kerja Wanita - Surilena Surilena; Mario Stefanus (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2005)
The Indonesian women labors who work abroad are prone to many kinds of violence. Many problems can occur to Indonesian Women Labors from mild to severe mental disorder. The Indonesian women labors bring income to Indonesia, that is why sending the women labors bring pros and contras in the Indonesian community. Violence againts the women labors can cause mental disorders. Mental disorders that can happen are Post Traumatic Stress Disorder, mild te severe depresion, anxiety disorder, alcogolic and drug abuse, acute psychotic disorder, and suicide.Key words : women labors - psychiatry aspects